2015
DOI: 10.1007/s11200-014-0146-5
|View full text |Cite
|
Sign up to set email alerts
|

3D electrical resistivity tomography technique for the investigation of a construction and demolition waste landfill site

Abstract: We present the practical application of a 3D electrical resistivity tomography (ERT) geophysical survey conducted in order to calculate the geometrical features and general structure of a construction and demolition waste layer in an old unregulated landfill prior to redevelopment. As traditional geological/geotechnical investigations comprised of cone penetration tests (CPT) failed to provide reliable results, primarily due to the nature of the underlying waste, a geophysical investigation was commissioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Non-invasive geophysical methods have been used extensively to investigate the composition and structure of the subsurface, and in particular electrical resistivity tomography (ERT) has been used for studying the landfills and related contaminated sites (Casado et al, 2015;Konstantaki et al, 2015;Slater and Binley, 2006;Vargemezis et al, 2015;Wang et al, 2015). The application of ERT for the study of the landfill sites addresses two main complimentary issues: (1) Mapping of extent of landfill sources (Bernstone et al, 2000;Ogilvy et al, 2002); and (2) Identification and mapping of landfill leachate plumes (Acworth and Jorstad, 2006;Perozzi and Holliger, 2008;Zume et al, 2006).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Non-invasive geophysical methods have been used extensively to investigate the composition and structure of the subsurface, and in particular electrical resistivity tomography (ERT) has been used for studying the landfills and related contaminated sites (Casado et al, 2015;Konstantaki et al, 2015;Slater and Binley, 2006;Vargemezis et al, 2015;Wang et al, 2015). The application of ERT for the study of the landfill sites addresses two main complimentary issues: (1) Mapping of extent of landfill sources (Bernstone et al, 2000;Ogilvy et al, 2002); and (2) Identification and mapping of landfill leachate plumes (Acworth and Jorstad, 2006;Perozzi and Holliger, 2008;Zume et al, 2006).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In recent years, one of the new developments is the use of 2D electrical imaging/tomography surveys to map areas with moderately complex geology and investigate landfill characterization [1]- [3] [5] [6]. In the study area, dipole-dipole resistivity survey was conducted to investigate any possible leakage and/or contamination.…”
Section: Dipole-dipole Resistivity Surveymentioning
confidence: 99%
“…electrical resistivity/induced polarization imaging, very low frequency-EM, and seismic refractionn tomography at Unguwan Dosa municipal solid waste-disposal site in Kaduna metropolis, North Western Nigeria to investigate ground water contamination. In 2015, reference [6] conducted 3D geoelectrical resistivity tomography (ERT) in an old unregulated landfill prior to redevelopment to calculate the geometrical features and general structure of a construction and demolition of a waste layer.…”
Section: Introductionmentioning
confidence: 99%
“…Jarvis (2011) presented a case of quarry reclamation for housing development in the United Kingdom by means of 38-m-high reinforced soil retaining walls with a face angle of 45°. Regarding site characterisation of building on waste disposal sites and infilled pits, a few cases were reported by Charles (2008), Skinner (2001, Vargemezis et al (2015) and Watts and Charles (2015). Santos et al (1998) utilised conventional geotechnical field testing, such as cone penetration tests (CPTs), standard penetration tests (SPTs) and plate load tests (PLTs) in determining geotechnical properties (settlement, Young's modulus and strength parameters) of solid waste materials.…”
Section: Introductionmentioning
confidence: 99%
“…Santos et al (1998) utilised conventional geotechnical field testing, such as cone penetration tests (CPTs), standard penetration tests (SPTs) and plate load tests (PLTs) in determining geotechnical properties (settlement, Young's modulus and strength parameters) of solid waste materials. Vargemezis et al (2015) found traditional CPT incapable of accurately detecting the interface between the waste materials and the host clay layer in a construction and demolition waste landfill site in northern Greece due to the impossibility of penetrating through the solid demolition debris. The geo-electric resistivity was, however, found more precise in the study by Vargemezis et al (2015) in estimating the thicknesses of the construction and demolition waste compared to the actual thicknesses verified by excavation of the landfill and removal of the debris.…”
Section: Introductionmentioning
confidence: 99%